Biofuels production and processing technology - Riazi, M. R.; Chiaramonti, David (CRC Press, Taylor & Francis Group, 2018)
The importance of biofuels in greening the transport sector in the future is unquestionable, given the limited available fossil energy resources, the environmental issues associated to the utilization of fossil fuels, and the increasing attention to security of supply. This comprehensive reference presents the latest technology in all aspects of biofuels production, processing, properties, raw materials, and related economic and environmental aspects. The book rounds out by describing properties, specifications, and quality of various biofuel products and new advances and trends towards future technology.